Can performance-related learning outcomes have standards? - Brockmann, Michaela [Verfasser]; Clarke, Linda [Verfasser]; Winch, Christopher [Verfasser] (My University, 2008)
"This paper aims to explain the distinction between educational standards and learning outcomes and to indicate the problems that potentially arise when a learning outcomes approach is applied to a qualification meta-framework like the European Qualification Framework, or indeed to national qualification frameworks. The methods used are documentary, political and conceptual analysis, with some reference to empirical work carded out in relation to other projects. It is found that there are substantial differences between learning outcomes and standards with large educational and political implications. Furthermore, the 'pure' form of learning outcomes approach contains a design flaw, which makes its coherent implementation problematic." (Autorenreferat, BIBB-Doku)
Keywords: S 2.2.5 Standards in der beruflichen Bildung; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Bildungsstandards; Lernergebnisorientierung; Europäischer Qualifikationsrahmen; Nationaler Qualifikationsrahmen; Europa